YOLOv9 – BASED TRAFFIC SIGN DETECTION UNDER VARYING LIGHTING CONDITIONS - Pangestu, Akbar; Putra, Muhammad Pajar Kharisma (Jurnal Teknik Informatika (Jutif), 2025)
Traffic signs are an important element that functions as a guide, regulator and safety supervisor for road users. In Indonesia, there are various types of traffic signs, including recommendation, prohibition, warning, command, and direction signs, which use numbers, letters, symbols, or a combination of the three to convey clear information to drivers. Based on data from the Indonesian National Police, 148,575 cases of traffic accidents were recorded in 2023, which continues to increase every day due to human error, poor road conditions, and lack of clarity and completeness of signs. This research aims to develop traffic sign detection technology using the YOLOv9 algorithm, starting with collecting 7,980 images from the Roboflow platform, which are then labeled and trained, and evaluated using metrics such as Accuracy, Precision, Recall, F1-Score, and Intersection over Union (IoU ). Then the model was tested to detect traffic signs in various media, such as images and videos. The results of this research show that the YOLO v9 model has the best performance compared to SSD MobileNet v2 and Faster RCNN. The YOLOv9 model achieved an accuracy of 94%, while SSD MobileNet v2 only had an accuracy of 43%, and Faster RCNN had an accuracy of 57%. From the research, it can be concluded that the YOLOv9 model is optimal enough to detect traffic signs in various lighting conditions, because the model has the best performance compared to the other two models, especially in terms of accuracy and balance between precision and recall. This research is expected to support the development of safer autonomous vehicles and intelligent transportation systems through optimal traffic sign detection.